Quantum Dot–Based FRET Immunoassay for HER2 Using Ultrasmall Affinity Proteins. Issue 35 (5th August 2018) - Wu, Yu‐Tang; Qiu, Xue; Lindbo, Sarah; Susumu, Kimihiro; Medintz, Igor L.; Hober, Sophia; Hildebrandt, Niko
Abstract: Engineered scaffold affinity proteins are used in many biological applications with the aim of replacing natural antibodies. Although their very small sizes are beneficial for multivalent nanoparticle conjugation and efficient Förster resonance energy transfer (FRET), the application of engineered affinity proteins in such nanobiosensing formats has been largely neglected. Here, it is shown that very small (≈6.5 kDa) histidine‐tagged albumin‐binding domain‐derived affinity proteins (ADAPTs) can efficiently self‐assemble to zwitterionic ligand–coated quantum dots (QDs). These ADAPT–QD conjugates are significantly smaller than QD‐conjugates based on IgG, Fab', or single‐domain antibodies. Immediate applicability by the quantification of the human epidermal growth factor receptor 2 (HER2) in serum‐containing samples using time‐gated Tb‐to‐QD FRET detection on the clinical benchtop immunoassay analyzer KRYPTOR is demonstrated here. Limits of detection down to 40 × 10 −12 m (≈8 ng mL −1 ) are in a relevant clinical concentration range and outperform previously tested assays with antibodies, antibody fragments, and nanobodies. Abstract : Polyhistidine‐mediated self‐assembly of engineered albumin‐binding domain‐derived affinity proteins (≈6.5 kDa, 1.0 × 1.5 × 2.5 nm 3 ) on semiconductor quantum dots allows for sensitive detection of HER2 by time‐gated Förster resonance energy transfer immunoassays.